Membrane computing : 17th International Conference, CMC 2016, Milan, Italy, July 25-29, 2016, Revised selected papers /: 17th International Conference, CMC 2016, Milan, Italy, July 25-29, 2016, Revised selected papers. (2017) - Unknown
No abstract available